2011
DOI: 10.1128/jvi.02223-10
|View full text |Cite
|
Sign up to set email alerts
|

Helix-Destabilizing, β-Branched, and Polar Residues in the Baboon Reovirus p15 Transmembrane Domain Influence the Modularity of FAST Proteins

Abstract: The fusogenic reoviruses induce syncytium formation using the fusion-associated small transmembrane (FAST) proteins. A recent study indicated the p14 FAST protein transmembrane domain (TMD) can be functionally replaced by the TMDs of the other FAST proteins but not by heterologous TMDs, suggesting that the FAST protein TMDs are modular fusion units. We now show that the p15 FAST protein is also a modular fusogen, as indicated by the functional replacement of the p15 ectodomain with the corresponding domain fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
(117 reference statements)
0
20
0
Order By: Relevance
“…Information on factors that stabilize or destabilize F protein TM interactions may therefore provide critical new insight into the triggering process. TM domain ␤-branched residues such as valine or isoleucine have been implicated in backbone dynamics and fusogenicity of peptides (68) and the fusion function of the reovirus fusion-associated small transmembrane proteins (61). ␤-Branched residues are present throughout the paramyxovirus F protein TM domains, and we have recently demonstrated that mutation of these residues can alter membrane fusion without affecting surface expression (64); however, the effect of these mutations on TM interactions remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Information on factors that stabilize or destabilize F protein TM interactions may therefore provide critical new insight into the triggering process. TM domain ␤-branched residues such as valine or isoleucine have been implicated in backbone dynamics and fusogenicity of peptides (68) and the fusion function of the reovirus fusion-associated small transmembrane proteins (61). ␤-Branched residues are present throughout the paramyxovirus F protein TM domains, and we have recently demonstrated that mutation of these residues can alter membrane fusion without affecting surface expression (64); however, the effect of these mutations on TM interactions remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Combining these data with the data from the C-terminal insertions (which immediately preceded the VIV sequence) suggests that ␤-branched residues in the sequence FVIV could be important modulators of F protein-promoted membrane fusion. Recent work with the baboon reovirus p15 TMD (15) and model peptides (34,35,60,61) suggests that ␤-branched residues are important in membrane fusion in a variety of systems. Nonpolar ␤-branched residues (valine and isoleucine) are traditionally thought of as being disruptive of ␣-helical structures; however, studies of synthetic peptides in detergent micelles demonstrated that these residues are incorporated into hydrophobic ␣-helices as easily as leucine (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…They assume a bitopic, N exoplasmic /C cytoplasmic topology in membranes, positioning very small (ϳ20 to 40 residues) fusion peptide-containing domains external to the plasma membrane (17)(18)(19)(20) and equalsized or considerably larger (ϳ36 to 141 residues) domains in the cytoplasm (21). The ecto-, endo-, and transmembrane domains all function as fusion modules and play an active role in the membrane fusion process (22,23).…”
Section: Importancementioning
confidence: 99%